THE USE OF SIMULATION AND LINEAR PROGRAMMING IN THE PLANNING OF AUDIT WORK (An Empirical Study in the Office of Financial Supervision) - حسن, ضوية سلمان; كاظم, هديل مهدي (Journal of Economics and Administrative Sciences, 2016)
Research includes three axes, the first is the average estimate time of achievement (day) to work oversight, to five supervisory departments in the Office of Financial Supervision Federal and then choose the three control outputs and at the level of each of the five departments above, and after analyzing the data statistically back to us that the distribution of the times of achievement It is the exponential distribution (Exponential Distribution) a parameter (q), and the distribution of normal (Normal Distribution) with two parameters (μ, σ2), and introduced four methods of parameter estimation (q) as well as four modalities parameter to estimate (μ) consistently (σ2), it was estimated average completion time for each of the (q) and (μ), and is considered each random variable has the distribution of initial potential is a function of the average number of sergeants (C), was a comparison between these modalities advantage in the practical side through simulation method using the Monte Carlo method ( Monte Carlo), and a number of users is important statistical measure of the experiences of the average error boxes (MSE) (Mean Square Error), it was in general to reach a good estimate (which has the lowest value of the average error boxes (MSE)) for each type of the three outputs regulatory and the level of all sizes samples (departments subject to regulatory scrutiny PET), and this is the estimated average is the optimum time for the completion of each type of audit reports and the corresponding optimal number of sergeants to accomplish this report.The second axis of research is planning to set a timetable for the completion of outputs control for the year 2009, as the table's goal is planning the completion of types of audit reports to chapters of the annual plan, and access to the optimum number for the completion of each type of reports as well as the regulatory power optimum (h / Sergeant) in order to be deviation ratios for the completion of the regulatory reporting less as possible by using linear programming, and after the implementation of the models on the program (TORA2006) reached an optimum number to complete the audit reports of various kinds, and each department of supervisory departments, according to the available resources as well as potential regulatory optimum (h / Sergeant) per season .Finally, the third axis, which included the proposal forms to improve the audit work, the first was (AWP circuits regulatory form for the period from 1/1/2009 until 31/12/2009), and the second (plan and follow up the inputs and outputs of the completion of audit work on the regulatory departments and bodies of the level of form ), which serves as compensation for five types of questionnaires prepared by the Department of Planning and Follow-up in the Office of Financial Supervision.